2021
DOI: 10.1029/2021gl095732
|View full text |Cite
|
Sign up to set email alerts
|

High Remanent Magnetization Measured in Hydrothermally Altered Lavas

Abstract: Magnetic surveys are used to identify and monitor hydrothermally altered regions on volcanoes. Commonly such magnetic data are interpreted on the premise that hydrothermal alteration consumes Fe‐Ti oxides in the host rocks, reducing their total magnetization. Here, we report a contrasting observation from Whakaari (White Island) volcano in New Zealand. We study the magnetic properties of 42 conduit‐filling and surficial lithologies that have undergone varying degrees of acid‐sulfate alteration. We find that wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 69 publications
0
4
0
1
Order By: Relevance
“…However, a complete transformation of the initial minerals removes the magnetic minerals and reduces magnetic susceptibility about two orders of magnitude (0.09•10 -3 SI for advanced altered andesitic lavas). Likewise, Kanakiya et al (2021) reported high remnant magnetization in altered lavas of the Whakaari geothermal field. This phenomenon can also be observed to some extent in our data (Fig.…”
Section: Petrophysical Properties-outcrop Vs Reservoir Samplesmentioning
confidence: 95%
See 1 more Smart Citation
“…However, a complete transformation of the initial minerals removes the magnetic minerals and reduces magnetic susceptibility about two orders of magnitude (0.09•10 -3 SI for advanced altered andesitic lavas). Likewise, Kanakiya et al (2021) reported high remnant magnetization in altered lavas of the Whakaari geothermal field. This phenomenon can also be observed to some extent in our data (Fig.…”
Section: Petrophysical Properties-outcrop Vs Reservoir Samplesmentioning
confidence: 95%
“…The reservoir samples can be grouped into (1) altered samples that still contain ferromagnetic minerals (10 -3 -10 -2 SI); (2) altered samples exhibiting magnetic susceptibilities reduced by about one to two orders of magnitude compared to group 1 (10 -3 -10 -4 SI); and (3) marbles, silicified lavas, and skarns showing a diamagnetic to paramagnetic behavior with magnetic susceptibilities that are up to three orders of magnitude smaller compared to group 1 (10 -4 -10 -6 SI). The loss of magnetic signals in the hydrothermally altered rocks could be used to identify and map the hydrothermal aureoles and thus, prospective fluid pathways in the reservoir using geophysics (e.g., borehole logs, airborne magnetic surveys; Kanakiya et al 2021).…”
Section: Petrophysical Properties-outcrop Vs Reservoir Samplesmentioning
confidence: 99%
“…Since my doctoral work in the Andes, my research has diversified to encompass a wide range of projects in numerous volcanic settings in the broad area of applied volcanology. For example, in the context of large, intermediate to silicic systems my recent PhD students have worked on exploring how the characteristics and distribution of tephra deposits can constrain numerical tephra hazard models (Constantinescu et al, 2021;Constantinescu et al, 2022), how hydrothermal alteration of rocks affects shallow plumbing systems and edifice stability (Kanakiya et al, 2021a;Kanakiya et al, 2021b;Kanakiya et al, 2022), and how pasture can be rehabilitated following large tephra falls (Sivarajan et al, 2020). A current student, Annahlise Hall, is exploring the explosive eruption history and hazards of the Tongan Volcanic Arc.…”
Section: My Research and The People Involvedmentioning
confidence: 99%
“…Daerah sekitar manifestasi panasbumi biasanya mengalami proses demagnetisasi akibat adanya alterasi pada sistem hidrotermal (Kanakiya et al, 2021). Nilai.…”
Section: Pendahuluanunclassified